Answer:
D
Step-by-step explanation:
Given the 2 equations
4x - 5y = 18 → (1)
3x - 2y = 10 → (2)
Multiplying (1) by 3 and (2) by - 4, then adding will eliminate the x- term
12x - 15y = 54 → (3)
- 12x + 8y = - 40 → (4)
Add (3) and (4) term by term to eliminate x, that is
- 7y = 14 ( divide both sides by - 7 )
y = - 2
Substitute y = - 2 into either of the 2 equations and solve for x
Substituting into (1)
4x - 5(- 2) = 18
4x + 10 = 18 ( subtract 10 from both sides )
4x = 8 ( divide both sides by 4 )
x = 2
solution is (2, - 2 ) → D
The result of simplifying the expression (x²/x⁻¹¹)¹/₃ using the exponent rules is
(x¹³)
To solve this exercise we have to resolve algebraic operations following the exponent rules.
(x²/x⁻¹¹)¹/₃
Using the quotient rule that indicates that: the exponent result will be the subtraction of these exponents, we have:
(x⁽²⁻⁽⁻¹¹⁾)¹/₃
(x⁽²⁺¹¹⁾)¹/₃
(x¹³)¹/₃
Using the power of a power rule that indicates that: the exponent result will be the multiplication of these powers, we have:
x⁽¹³*¹/₃⁾
x⁽¹³/₃⁾
As we have a fractional exponent, you must convert the exponent to root:
(x¹³)
<h3>What is an exponent?</h3>
In mathematics an exponent is the number of time that a number, called (base) is multiplied by itself. It is also called, power or index.
Example: 3² = 3*3 = 9
Learn more about exponent at: brainly.com/question/847241
#SPJ4
Answer:
1
Step-by-step explanation:
hope this help:) I use slop formula
1 cm is the base of the triangle